2007
DOI: 10.1002/tox.20267
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the toxicity and genotoxicity of cadmium in amphibian larvae (Xenopus laevis and Pleurodeles waltl) using the comet assay and the micronucleus test

Abstract: The toxic and genotoxic potential of Cadmium (CdCl(2)) were evaluated by the micronucleus test (MNT) and comet assay (CA) using amphibian larvae (Xenopus laevis and Pleurodeles waltl). Acute toxicity results showed that Cd is toxic to Xenopus larvae exposed from 2 to 50 mg/L and to Pleurodeles from 5 to 50 mg/L, depending on the nature of the water (reconstituted water containing mineral salts or mineral water MW (Volvic)). The MNT results obtained in MW showed that Cd (2 mg/L) is genotoxic to Xenopus, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 74 publications
2
32
0
Order By: Relevance
“…This may be different between species and cellular processes (i.e. metabolization/detoxication) (Gauthier et al 2007). As with many pesticides, the potential genotoxic effect of diuron appears to be mediated by the production of oxyradicals during biotransformation processes.…”
Section: Sensitivity Of Palaemon Serratus Spermatozoa Toward Genotoximentioning
confidence: 99%
“…This may be different between species and cellular processes (i.e. metabolization/detoxication) (Gauthier et al 2007). As with many pesticides, the potential genotoxic effect of diuron appears to be mediated by the production of oxyradicals during biotransformation processes.…”
Section: Sensitivity Of Palaemon Serratus Spermatozoa Toward Genotoximentioning
confidence: 99%
“…The SCGE test has become extensively valuable as a biomarker in amphibians to monitor contaminated areas (in situ assay) (Burlibasa and Gavrila, 2011;Maselli et al, 2010), as well as for the screening of xenobiotics after direct or indirect exposure (in vivo assay) (Mouchet et al, 2007;Nikoloff et al, 2014b;Pérez-Iglesias et al, 2014;Ruiz de Arcaute et al, 2014). We observed that, regardless of the length of treatment, IMZT acute exposure within the 0.39-1.17 mg/L concentration range increased the frequency of primary DNA lesions estimated by alkaline SCGE, a result opposite that of the MN test.…”
Section: Figmentioning
confidence: 99%
“…have been well documented in a wide range of different species: teratogenesis in Xenopus laevis (Mouchet et al 2006(Mouchet et al , 2007 and carcinogenesis in Syrian hamsters are useful examples of its toxicity (Waalkes and Rehm 1998). In addition, cadmium is irreversibly accumulated into cells, as it has been demonstrated in rat organs and marine mollusks (Roesijadi et al 1996;Haouem et al 2007).…”
mentioning
confidence: 96%